Kinetic model of poly(3-hydroxybutyrate) thermal degradation from experimental non-isothermal data - Santos, A. F. [UNESP]; Polese, L. [UNESP]; Crespi, Marisa Spirandeli [UNESP]; Ribeiro, Clovis Augusto [UNESP] (Springer, 2009)
The non-isothermal data given by TG curves for poly(3-hydroxybutyrate) (PHB) were studied in order to obtain a consistent kinetic model that better represents the PHB thermal decomposition. Thus, data obtained from the dynamic TG curves were suitably managed in order to obtain the Arrhenius kinetic parameter E according to the isoconversional F-W-O method. Once the E parameters is found, a suitable logA and kinetic model (f(alpha)) could be calculated. Hence, the kinetic triplet (E +/- SD, logA +/- SD and f(alpha)) obtained for the thermal decomposition of PHB under non-isothermal conditions was E=152 +/- 4 kJ mol(-1), logA=14.1 +/- 0.2 s(-1) for the kinetic model, and the autocatalytic model function was: f(alpha)=alpha(m)(1-alpha)(n)=alpha(0.42)(1-alpha)(0.56).
Keywords: biodegradable polymers; non-isothermal kinetic; PHB thermal degradation